MANAJEMEN PEMBIAYAAN PENDIDIKAN DI LEMBAGA PAUD NUSA INDAH TARATAK TANAH GARAM KOTA SOLOK - Nofri Bakri; Muhammad Fazis; Nurlaila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The focus of this study is Financing Management at the Nusa Indah Taratak Tanah Garam PAUD Institution, Solok City. This study aims to: 1) Determine the financing planning at the Nusa Indah Taratak Tanah Garam PAUD Institution, Solok City; 2) Determine the implementation of financing at the Nusa Indah Taratak Tanah Garam PAUD Institution, Solok City; and 3) Determine the evaluation of financing at the Nusa Indah Taratak Tanah Garam PAUD Institution, Solok City. This research method is qualitative which is located at the Nusa Indah Taratak PAUD. Data collection techniques through interviews, observations, and documentation. Data processing is carried out descriptively qualitatively, then described and classified certain aspects and explained through effective sentences. The results of this study indicate that: 1) At the planning stage of education financing at the Nusa Indah Taratak PAUD, it has been implemented well and transparently. 2) At the stage of financing implementation at PAUD Nusa Indah Taratak, it has been running well because it follows two things, namely receipt and expenditure activities, in the implementation of financing it has referred to the RKAS, which is responsible for implementing financing, namely the Head of Unit as the Budget Holder Authority (KPA) assisted by the Treasurer under the supervision of the Manager. 3) The evaluation stages of financing at PAUD Nusa Indah Taratak, Solok City have been carried out optimally. After the school needs spending activities were carried out, a meeting was held in order to prepare a Report. The Solok City Education Office also participated in monitoring the location of the institution to check evidence related to the use of BOP funds. The form of accountability for educational financing at PAUD Nusa Indah Taratak, Solok City includes making reports.